Information Design for Education - Coutinho, Solange Galvão (InfoDesign, 2006)
This paper presents the intrinsic relationship between Information Design and Education through the study of graphic artefacts. The aim is to present some disquieting aspects concerning the concepts of Art at school, the use of image and, the state of educational artefacts within Brazilian schools. This work also suggests a reflection on the past in order to understand the nature of the conflicting relation between the form and contents of such artefacts. Investigations are also presented concerning information design research for early education conducted at the Design Department of the Federal University of Pernambuco, bringing to surface a discussion upon the responsibility of the Information Designer in such a matter.